Pharmacokinetics of benapenem for injection in subjects with mild to moderate renal impairment. - Yang, Haijing; Zhang, Min; Chen, Yuancheng; Ren, Hong; Zhang, Hong; Yu, Chen; Lu, Jianda; You, Li; Yu, Jicheng; Liang, Hong; Xiao, Cuilan; He, Zishuang; et al. (European Journal of Clinical Pharmacology, 2022)
Objective: This study evaluated the pharmacokinetic (PK) characteristics of benapenem in subjects with mild to moderate renal impairment to provide a reference for benapenem dosing regimens in this patient population. Methods: Eighteen subjects were enrolled in this study. Each subject received a single dose of benapenem intravenously (1.0 g in 100 ml of 0.9% saline) followed by blood and urine collection to measure the concentrations of benapenem and its major metabolite. PK analysis was performed to evaluate the effect of varying degrees of renal impairment on the PK characteristics of benapenem. The safety of benapenem was also evaluated. Results: In subjects with normal renal function, mild renal impairment, and moderate renal impairment, the maximum plasma benapenem concentrations were 163 ± 6.58 mg/L, 138 ± 17.4 mg/L, and 134 ± 0.11 mg/L, respectively (15.3% and 17.8% lower in subjects with mild and moderate renal impairment, respectively, than in subjects with normal renal function). The areas under the plasma concentration–time curve (AUC0-inf) were 1153.67 ± 143.2 mg·h/L, 1129.17 ± 241.41 mg·h/L, and 1316.46 ± 229.83 mg·h/L, respectively (P > 0.05); the cumulative urinary excretion rates at 72 h after dosing were 52.61 ± 8.58%, 39.42 ± 8.35%, and 29.84 ± 9.15%, respectively; and the metabolic ratio (AUC0-inf_KBP-3331/AUC0-inf_benapenem) were 3.96 ± 0.35%, 5.56 ± 0.82%, and 8.24 ± 0.85%, respectively. No drug-related adverse events (AEs), serious AEs, or AEs leading to withdrawal occurred in this study. Conclusion: No adjustment to benapenem dosing is needed in patients with mild to moderate renal impairment. Clinical trial registration: Drug clinical trial registration and information publicity platform: http://www.chinadrugtrials.org.cn/index.html. Registration number: CTR20190760.